Sustainable social spending in a greying economy with stagnant public services: Baumol's cost disease revisited - Frederick van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2006)
Baumol's cost disease states that relatively high productivity growth in manufacturing induces a steady increase in the relative price of human services. If demand for these services is inelastic or manufactured goods are necessities, the budget share of these services inexorably rises over time and labour gradually shifts from manufacturing to services. If the care for children and elderly releases time for households, labour supply and the budget share of human services expand over time. This paper addresses the sustainability of human services such as care and education in a greying economy if they are financed by labour taxes. A productivity growth differential in favour of the market sector pushes up the tax rate and public sector employment if private goods and public services are poor substitutes, labour supply is relatively inelastic and there are not too many pensioners and children. Private affluence and public squalor result if labour supply is very elastic, the dependency ratio is large and the market provides good substitutes for public services. Greying of the population boosts demand for public employment if the market provides poor substitutes for public services, but the provision of public services per dependent may fall due to the erosion of the tax base. Subsequently, we discuss the situation where market and public employment are imperfect substitutes for households, the utility of money is not constant and public sector productivity depends on public sector pay.
Keywords: E62; H0; J22; J31; J4; O40; 330